Everyday interactions and political participation of Malaysian youth - Ting, Su Hie; Sharifah Sophia, Wan Ahmad (Informa UK Limited, 2021)
Some scholars have argued that youth apathy in politics arises from an interpretation based on conventional electoral politics. Other scholars have studied unconventional political participation and found the willingness of youth to sign petitions, join boycotts, and attend demonstrations. However, little is known about the potential of everyday interactions to generate youth interest in politics. This study examined youth participation in politics, including everyday interactions, before the 14th general election in Malaysia which changed the ruling government after six decades. Semi-structured interviews were conducted with 28 participants aged 15–40 from lower socio-economic backgrounds. Analysis revealed low levels of political participation in electoral politics. Less than half of them voted in campus elections, and state or parliamentary elections, or attended campaign rallies. None of them were candidates in campus elections, and none of their immediate family members were political candidates. A majority of the participants were engaged in everyday interactions through online news, occasional political conversations with friends, teachers, lecturers and parents, membership in organisations, and writing letters to government agencies. The findings suggest that youth disengagement from politics is due to a closed political climate, and the perception of politics as dirty and for the self-gain of politicians.